Expressive Speech in the Comment Column on the Instagram Account @infopku - Fitri Matrona Simanullang; Fatmawati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The aim of this research is to find out and describe the expressive speech used by netizens in the comment’s column of the Instagram account @infopku_. This research uses a qualitative descriptive methodology. The data source in this research is comments on the Instagram post @infopku_ on Wednesday 08 May 2024 regarding